Peran Konten Dakwah Media Sosial dalam Membentuk Identitas Keislaman Remaja di Kota Blitar - Afif Muhtar, Alvin; rohman, miftakhul (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2024)
The problem facing teenagers today is the Islamic identity crisis, which is largely caused by the influence of external culture through social media. Based on the results of observations, it was found that parents and educators' concerns about adolescent behavior are increasing, especially with the number of cases such as juvenile delinquency and criminal acts. Therefore, efforts are needed to help teenagers understand religious lessons well and in depth. This research uses qualitative methods which aim to describe the concepts and conditions of teenagers, the influence of the media on their development, and how preaching content on social media can help shape Islamic identity. The aim of this research is to examine the role of social media in building the Islamic identity of teenagers in Blitar City. The object of the research involved teenage students attending school in Blitar City. The results of the research show that preaching content on social media has an important role in forming Islamic identity through Islamic religious education among teenagers. The survey results regarding satisfaction with teenagers' use of social media showed that 72.4% were satisfied, 17.2% were very satisfied and 10.3% were dissatisfied. Interesting and relevant content makes it easier for teenagers to understand the material more quickly compared to other content. Apart from that, teenagers become more tolerant towards other religions and phenomena that are not in line with their understanding. By using social media wisely and creating propaganda content that supports harmony, culture and harmony between groups can be maintained.